Mothering heights ebook - Pilkey, Dav (Dog Man, 2021)
Dog Man and Petey face their biggest challenges yet in the tenth Dog Man book from worldwide bestselling author and illustrator Dav Pilkey. Dog Man is down on his luck, Petey confronts his not so purr-fect past, and Grampa is up to no good. The world is spinning out of control as new villains spill into town. Everything seems dark and full of despair. But hope is not lost. Can the incredible power of love save the day? Dav Pilkey's wildly popular Dog Man series appeals to readers of all ages and explores universally positive themes, including love, empathy, kindness, persistence, and the importance of doing good.